Assessment of Sustainable Utilization of Ecosystem Services in Different Stages of Mangrove Forest Restoration at Klong Khone Sub-district, Samut Songkhram Province, Thailand - Adulcharoen, Wipapan; Suntornvongsakul, Kallaya; Lee, Yang-Soo (Applied Environmental Research, 2020)
Understanding the function of the ecological restoration of mangrove forests leads to appropriate sustainable utilization (SU) of ecosystem services (ES) during development stages of mangrove ecosystem for sustaining the local livelihood and maintaining the mangrove ecological production. The study aims to identify the SU which was changed relying a development of ES at Klong Khone (KK) Sub-district, Samut Songkhram Province, Thailand. The SU was collected by in-depth interview with 20 key respondents, questionnaires survey with 140 fishermen and statistical scientific data on developed mangrove forest areas. Descriptive statistics and event analysis were employed to analyze the data. The study found that bottom-up management tools based on a local people’s participation were applied to determine a way of harvest of ES. An application of these local tools including a common property right, land use zoning, application of local knowledge, human resources, and financial and technological transfer resulted in different utilizing activities of ES during the development of mangrove forest restoration stages. The results showed that the ES produced during mangrove stand initiation stage were mainly harvested for food (90%) and during the young forest regrowth stage (87%) (N = 140). They were also widely used for operating aquaculture during mangrove stand initiation stage (39%), but they were harvested with more concerns about environmental impacts during the young forest regrowth stage (47%) (N = 140). The cultural services during young forest regrowth stage were increasingly utilized for diversified incomes from ecotourism (46%) and education learning program (50%) (N = 140). The ES from developed mangrove forest were harvested effectively based on an application of SU tools which were locally developed by local people’s participation. The SU tools can be proposed and applied in other communities where have similar ecological, social and cultural conditions as KK sub-district to support the SU of ES.